The impact of depression and anxiety on the correlation between somatic symptom disorder and subjective cognitive decline in the Chinese elderly population: an exploration by simple, serial, and moderated mediation models - Yongsen Lin; Pingzhen Lin; Guiying Zeng; Shufang Wu; Ronghua Chen; Yingchun Xiao; Hongbin Chen (Frontiers in Psychology)
BackgroundSomatic symptom disorder (SSD) exacerbates subjective cognitive decline (SCD). This association can be significantly impacted by the mental well-being of the SSD patients. However, the underlying mechanisms remain obscure.MethodsA total of 525 elderly patients, who visited the Department of Neurology of Fujian Medical University Union Hospital between October 2017 and August 2024, and the Department of Neurology of Quanzhou First Hospital Affiliated to Fujian Medical University between August 2022 and August 2024, were included in the study. Data of sociodemographics, medical history, somatic symptom disorder, subjective cognitive decline, depression, and anxiety were analyzed by simple, serial and moderated mediation models to evaluate the impact of depression and anxiety on the linkage between SSD and SCD.ResultsSSD significantly affected SCD. Simple mediation analysis showed that depression and anxiety significantly mediated the association between SSD and SCD (βdepression = 0.079, 95% CI: 0.030 to 0.132; βanxiety = 0.058, 95% CI: 0.031 to 0.093). Serial mediation analyses indicated that the worsening of SSD exacerbates anxiety, in turn aggravating depressive symptoms and SCD (βb = 0.044, 95% CI: 0.026 to 0.069). Moderated mediation model revealed that the depressive symptoms-conferred mediation of the correlation between SSD and SCD was moderated by anxiety symptoms (β = −0.073, 95% CI: −0.131 to −0.014).ConclusionThese findings provided new insights into possible avenues for prevention and intervention of SCD through SSD-based treatments with a multifaceted approach to psychiatric disorders.